Cyclosporine-induced immune suppression alters establishment of HTLV-1 infection in a rabbit model - Haynes, Rashade A. H. (American Society of Hematology, 2010)
Human T-lymphotropic virus type 1 (HTLV-1) infection causes adult T-cell leukemia and several lymphocyte-mediated inflammatory diseases. Persistent HTLV-1 infection is determined by a balance between host immune responses and virus spread. Immunomodulatory therapy involving HTLV-1–infected patients occurs in a variety of clinical settings. Knowledge of how these treatments influence host-virus relationships is not understood. In this study, we examined the effects of cyclosporine A (CsA)–induced immune suppression during early infection of HTLV-1. Twenty-four New Zealand white rabbits were split into 4 groups. Three groups were treated with either 10 or 20 mg/kg CsA or saline before infection. The fourth group was treated with 20 mg/kg CsA 1 week after infection. Immune suppression, plasma CsA concentration, ex vivo lymphocyte HTLV-1 p19 production, anti–HTLV-1 serologic responses, and proviral load levels were measured during infection. Our data indicated that CsA treatment before HTLV-1 infection enhanced early viral expression compared with untreated HTLV-1–infected rabbits, and altered long-term viral expression parameters. However, CsA treatment 1 week after infection diminished HTLV-1 expression throughout the 10-week study course. Collectively, these data indicate immunologic control is a key determinant of early HTLV-1 spread and have important implications for therapeutic intervention during HTLV-1–associated diseases.